Postweaning exposure to gossypol results in epididymis-specific effects throughout puberty and adulthood in rats - Romualdo, G. S.; Klinefelter, G. R.; Kempinas, W. D. (Amer Soc Andrology, Inc, 2002)
Gossypol, a yellow pigment found in cottonseeds, well known for its antifertility properties in animals, has been used as a contraceptive by men. The aims of this work were to evaluate the effects of gossypol throughout sexual development of male rats and to provide additional data to clarify the target site or sites of this compound in the male reproductive system, Gossypol (15 mg/kg per day) was given to animals from weaning through prepuberty (41 days), early puberty (51 days), puberty (61 days), and sexual maturity (91 days). Ventral prostate weight and fructose levels were similar in control and treated rats, suggesting that androgen levels were normal. No histological effects on the testis were detected, but there was a significant decrease in the sperm concentration in the cauda epididymidis of gossypol-treated animals killed at 61 and 91 days, as well as a significant increase in abnormal sperm in the vas deferens of treated animals. Moreover, the histology of the cauda epididymidis of the rats treated throughout puberty (ie, until days 51 and 61) showed a great number of round bodies in the lumen of the epididymis. These structures stained for the epididymis-specific protein E. Collectively, the data demonstrate that the epididymis is a target of gossypol when postweaning exposure extends throughout pubertal development, and that whereas more subtle histological effects commence around puberty, indicators reproductive competence are compromised in adulthood.
Keywords: male reproduction; sexual development; sperm maturation; male contraception